The Millennial graduate student: implications for educators in the fashion discipline - Kozar, Joy M.; Hiller Connell, Kim (My University, 2014)
The purpose of this study was to expand upon an overall understanding of today’s Millennial graduate student. Information related to the motivations of Millennial generation students in pursuing master’s degrees in fashion programs were collected, in addition to analysing the expectations of Millennial students while in graduate programs. Participants included both master’s-level graduate students enrolled in fashion programs and graduate faculty at the students’ home institutions. The similarities and expectations among students and faculty were identified. A major finding was that Millennial graduate students are primarily motivated by industry-related career goals, and do not perceive conducting empirical research as central to their education. The educational implications for graduate faculty based on the findings of this study are addressed, noting areas of educational reform and additional research.
Keywords: Fashion programs; Graduate studies; Master’s degree; Millennials